Protocol for an undergraduate student-led scoping review of methods used to conduct inclusive focus groups with autistic adolescents - Nivedita Medum; Trevor Stocker; Mary Finkler; Júlia Hellín López; Noah Edwards; Makenna Sommers; Morgan Gaston; Ella Marie Johnson; Amanda Schadler; Josh Byars; Julia Griese; Celeste Campos-Castillo (PLoS ONE, 2025)
Although focus groups gather early-stage input effectively, our initial literature review found few focus group studies conducted with autistic adolescents (ages 12–19), despite the potential for focus groups to provide a safe, peer-based setting that encourages autistic adolescent engagement in research. Scoping reviews of focus groups for children and people with disabilities exist, but not for autistic adolescents. We aim to fill this gap. Consequently, we plan to conduct a scoping review to identify the methods used to design inclusive focus groups for autistic adolescents. Because few relevant studies exist, we describe steps to search both academic databases and online sources (X, YouTube, Google). We detail how we will leverage our team composition, which is led by a large group of undergraduate students, some of whom are neurodiverse, to enhance the rigor and reproducibility of the scoping review. These steps include accounting for algorithms personalizing search results from online sources and the risk of encountering false information that could cause harm. We will analyze the results to show 1) the extent to which focus groups on autistic adolescents are conducted with autistic adolescents; 2) characteristics of autistic adolescents included in focus groups and underrepresented populations; 3) steps taken to design accessible focus groups for autistic adolescents; 4) which methods were feasible for and acceptable to autistic adolescents. The results of our scoping review will be an important step toward including input from autistic adolescents in the early stages of a project and, more broadly, in the research process.